2018
DOI: 10.3389/fvets.2018.00131
|View full text |Cite
|
Sign up to set email alerts
|

Personality Research in Mammalian Farm Animals: Concepts, Measures, and Relationship to Welfare

Abstract: Measuring and understanding personality in animals is a rising scientific field. Much research has been conducted to assess distinctive individual differences in behavior in a large number of species in the past few decades, and increasing numbers of studies include farm animals. Nevertheless, the terminology and definitions used in this broad scientific field are often confusing because different concepts and methods are used to explain often synonymously applied terms, such as personality, temperament and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 165 publications
4
103
1
1
Order By: Relevance
“…The relationship between aggressiveness and personality traits measured in tests other than the backtest has less often been investigated. The response in the human approach test, commonly used to assess fear tendency (Finkemeier et al, 2018), was poorly correlated (Scheffler et al, 2016a) or not correlated (Janczak et al, 2003) with aggressiveness observed in rearing pens. Gilts classified as low or high responders after several behavioural tests (including restraint, handling, sudden human approach) did not differ in their number of attacks towards other gilts in a food competition test (Lawrence et al, 1991).…”
Section: Influence Of Personality and Coping Style On Biting Behavioursmentioning
confidence: 92%
See 2 more Smart Citations
“…The relationship between aggressiveness and personality traits measured in tests other than the backtest has less often been investigated. The response in the human approach test, commonly used to assess fear tendency (Finkemeier et al, 2018), was poorly correlated (Scheffler et al, 2016a) or not correlated (Janczak et al, 2003) with aggressiveness observed in rearing pens. Gilts classified as low or high responders after several behavioural tests (including restraint, handling, sudden human approach) did not differ in their number of attacks towards other gilts in a food competition test (Lawrence et al, 1991).…”
Section: Influence Of Personality and Coping Style On Biting Behavioursmentioning
confidence: 92%
“…Background. Personality is defined by a correlated set of individual behavioural and physiological traits that are consistent over lifetime and environmental contexts (Finkemeier et al, 2018). In humans, personality is described by five main dimensions.…”
Section: Influence Of Personality and Coping Style On Biting Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to prior experiences, temperament may affect cognitive processes through its influence on emotional state, and consequently attention, memory and judgement [15,21]. For example, fearfulness (i.e., high emotional arousal to a challenging situation; Finkemeier et al [22]) is a feature of animal temperament [23][24][25] that has been associated with impaired learning in calves [26]. Fear can be induced by unpleasant events that are sudden, unfamiliar, unpredictable and inconsistent with expectations [27].…”
Section: Introductionmentioning
confidence: 99%
“…In our study populations of elk, the apparent importance of predation risk to the occurrence of behavioral types made it surprising that we found a similar gradient of shy through bold individuals in a captive elk population, where predators were effectively absent and forage was uniformly available (Found and St. Clair, 2016). Evidence of personality is similarly apparent for several domestic species (Finkemeier et al, 2018), many of which are also protected from natural predators. More generally, behavioral types appear to result from complex geneenvironment interactions that involve multiple, pleiotropic genes (Bouchard and Loehlin, 2001;Krueger et al, 2008) that persist in all populations owing to variable or changing environments (Dingemanse et al, 2007) and both frequency and densitydependent effects (Aplin et al, 2014;Nicolaus et al, 2016).…”
Section: Review Of Personality and Migration In Wild Elkmentioning
confidence: 58%